Constitutional Rights and Environmental Protection in Indonesia from a Legal and Policy Perspective - Susanto, Aris; Baralaska, Sapto; Jaelani, Aan (Ann Publisher, 2024)
This research explores the relationship between constitutional rights and environmental protection in Indonesia from a legal and policy perspective. Environmental protection has been recognized as part of the human rights guaranteed by the Indonesian constitution. This study uses a qualitative approach with a descriptive-analytical method, relying on data from literature studies, legal documents, and relevant public policies. The results show that despite the constitutional recognition of the right to a good and healthy environment, implementation on the ground still faces many challenges. These challenges include weak enforcement of environmental laws, lack of coordination between government agencies, and conflicts of interest between economic development and environmental conservation. This study recommends increasing the capacity of law enforcement institutions, improving regulations, and community involvement in the environment-related decision-making process to strengthen the protection of constitutional rights to the environment in Indonesia.